Anatomical Variations, Oxidative Stress, and Cardiac Dysfunction as Predictors of Postoperative Complications in Pediatric Abdominal Surgery: A Clinical Study - Adina Qaiser, Hafsa Liaqat, Arshad Kamal, Rabea Nasir, Asad Shameem, Attique Afzal Malik, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pediatric abdominal surgery carries a substantial risk of postoperative complications due to developmental anatomical differences, variable physiological reserves, and potential underlying organ dysfunction. Emerging evidence suggests that congenital anatomical variations, oxidative stress imbalance, and subclinical cardiac dysfunction may collectively influence postoperative outcomes in children. Objective: To evaluate the predictive role of anatomical variations, oxidative stress biomarkers, and cardiac dysfunction in determining postoperative complications among pediatric patients undergoing abdominal surgery. Methods: This prospective clinical study included 100 children aged 1–14 years who underwent abdominal surgery at Lady Reading Hospital, Peshawar, and Tehsil Headquarters Hospital, Ahmed Pur East, from June 2022 to June 2023. Preoperative assessment comprised anatomical imaging, oxidative stress markers malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GPx) and echocardiographic evaluation of cardiac function. Postoperative complications were monitored for 30 days. Multivariate logistic regression was used to identify predictors. Results: Anatomical variations were present in 37% of patients and were significantly associated with higher complication rates (p = 0.001). Children who developed complications showed elevated MDA and reduced SOD and GPx levels (p < 0.01). Subclinical cardiac dysfunction was identified in 23% and was strongly associated with cardiopulmonary instability and ICU admission (p < 0.01). A combined predictive model incorporating all three parameters demonstrated excellent accuracy (AUC = 0.92; sensitivity 87%, specificity 81%). Conclusion: Anatomical anomalies, oxidative stress dysregulation, and subclinical cardiac dysfunction are significant predictors of postoperative complications in pediatric abdominal surgery. Integrating these assessments into preoperative evaluation may improve risk stratification and surgical outcomes. Keywords: Anatomical variations, oxidative stress, cardiac dysfunction, pediatric abdominal surgery, postoperative complications.